Ubiquitin Modification Patterns of Clear Cell Renal Cell Carcinoma and the Ubiquitin Score to Aid Immunotherapy and Targeted Therapy - Zhou, Peng; Lu, Yuchao; Xun, Yang; Xu, Jinzhou; Liu, Chenqian; Xia, Qidong; Lu, Junlin; Wang, Shaogang; Hu, Jia (Frontiers in Cell and Developmental Biology, 2021)
Ubiquitin modification is the most common protein post-translational modification (PTM) process in organisms, and 1332 ubiquitin regulators have been identified in humans. Ubiquitin regulators, especially E3 ligases and deubiquitinases, are widely involved in immune processes. This study aims to explore the ubiquitin modification features of clear cell renal cell carcinoma (ccRCC) and to elucidate the role of such ubiquitin modifications in shaping anti-tumor immunity and individual benefits from immune checkpoint blockade (ICB). A comprehensive analysis was performed in the TCGA cohort (n = 530) and GEO cohort (n = 682). RNA sequencing data of 758 differentially expressed regulators, which was validated by the proteomic data, were used for k-means unsupervised consensus clustering and three ubiquitin patterns of ccRCC were identified. Then, we focused on the ubiquitin modification and tumor progression signatures, immune infiltration characteristics, and prognostic value. The three patterns with different ubiquitin modification signatures correspond to "immune desert phenotype", "immune resistance phenotype" and "immune-inflammatory phenotype", respectively. To facilitate clinical application, we constructed a ubiquitin score to evaluate individual patients` ubiquitination outcome, and it was demonstrated to be an independent risk factor for overall survival (OS) in multivariate cox analysis. It was found that high score group was correlated to higher immune cells infiltrating level and PD-1/PD-L1/CTLA-4 expression. More importantly, we found that the high score group was predicted to be sensitive to anti-PD-1 treatment, while the low-score group showed lower predicted IC50 values in treatment with Pazopanib and Axitinib. In summary, this study elucidated the potential link between ubiquitin modification and immune infiltration landscape of ccRCC for the first time and provided a new assessment protocol for the precise selection of treatment strategies for patients with advanced ccRCC.